Fifth World Congress of Sports Physical Therapy Scientific Abstracts - International Federation of Sports Physical Therapy; NFFs Faggruppe for Idrettsfysioterapi og Aktivitetsmedisin; International Journal of Sports Physical Therapy (North American Sports Medicine Institute, 2024)
The International Journal of Sports Physical Therapy is pleased to publish abstracts from the 5th World Congress of Sports Physical Therapy, which will take place in Oslo, Norway, June 14-15, 2024. The theme of the Congress is "From Science To Clinical Practice." The variety of presentations during this congress are examples of the contemporary sports physical therapy research activities taking place around the world. The abstracts presented in the following pages were selected by the Scientific Committee, which included members from the International Federation of Sports Physical Therapy. It should be noted that abstracts have not been reviewed by the Editorial Board, Associate Editors or Editor-in-Chief of the International Journal of Sports Physical Therapy. After careful review by an international team of reviewers, research abstracts will be presented by authors at the World Congress. Each abstract presents only a brief summary of a research project / presentation and does not permit full assessment of the scientific rigor with which the work was conducted. While the abstracts offer only preliminary results that may require further refinement and future validation, they do serve an important role of sharing new research ideas from around the world. This sharing of ideas helps to encourage worldwide dialogue among researchers, clinicians, and educators that will ultimately contribute to the sports physical therapy body of knowledge. Notice: The abstracts below are presented as prepared by the authors. The accuracy and content of each abstract remain the responsibility of the authors.